Factors Affecting Online Purchase Decisions At Hello Kitty Shop Bengkulu City - Anita Septia Dewi; Suwarni; Kaulan (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The purpose of the study is to find out the most dominant factor affecting online purchasing decisions in Rumah Hello Kitty shop of Bengkulu City. The sample in this study was 56 consumers who buy in online in Rumah Hello Kitty shop of Bengkulu City. Sampling is done by accidental sampling technique. The data collection method used is questionnaires and the analytical method used is the analysis scale. The results of this study show that the average perceptions of respondents towards factors affecting online purchasing decisions in Rumah Hello Kitty shop of Bengkulu City are as much as 1,370.5 with the agreed assessment criteria. The meanings of the respondents changed the factors affecting online purchasing decisions in Rumah Hello Kitty shop of Bengkulu City are cultural, social, personal and psychological factors. Personal factors are the most dominant factors affecting online purchasing decisions with a total score of perception of 1,466, in very much agreed criteria. The lowest factor affecting online purchasing decisions in Rumah Hello Kitty shop of Bengkulu City is cultural with a total score of perception of 1,285, with agreed criteria.